2008
DOI: 10.1158/1535-7163.mct-07-0570
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of metaplastic breast carcinoma: high EGFR copy number via aneusomy

Abstract: Metaplastic breast carcinoma, a rare tumor composed of adenocarcinomatous and nonglandular growth patterns, is characterized by a propensity for distant metastases and resistance to standard anticancer therapies. We sought confirmation that this tumor is a basal-like breast cancer, expressing epidermal growth factor receptor (EGFR) and stem cell factor receptor (KIT). EGFR activating mutations and high copy number (associated with response to tyrosine kinase inhibitor gefitinib) and KIT activating mutations (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 34 publications
4
61
0
1
Order By: Relevance
“…The tumors were rich in mitotic figures with an average mitotic count of 31/10 HPFs. The histopathological features observed in our series are similar to the description in the previous studies (4,5,7,15,16,21,22). in addition, 3 cases had a central scar, 5 had central necrosis, 7 had geographic necrosis and 6 had a pushing growth pattern.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The tumors were rich in mitotic figures with an average mitotic count of 31/10 HPFs. The histopathological features observed in our series are similar to the description in the previous studies (4,5,7,15,16,21,22). in addition, 3 cases had a central scar, 5 had central necrosis, 7 had geographic necrosis and 6 had a pushing growth pattern.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, an immunohistochemical panel, proposed by Carey et al, including estrogen receptor (Er), progesterone receptor (Pr), human epidermal growth factor receptor-2 (HEr2), epidermal growth factor receptor (EGFr) and cytokeratin 5/6 (CK 5/6), was widely accepted for use in identifying breast carcinomas with basal-like immunophenotype as defined by cDna microarrays (12). in the meantime, MCs have been shown to be a part of the spectrum of basal-like breast carcinomas, since they usually display a basal/myoepithelial and epithelial to mesenchymal molecular make-up (13,14), basal-like immunophenotype, and triple negativity and often show expression of EGFr, CK14 and CK5/6 (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…[42], CD44 [43] and epidermal growth factor receptor (EGFR) [36]. In a minority of cases, they harbour EGFR gene amplification [8] or aneusomy [44]. Basal-like tumours may express genes characteristic of luminal epithelia, including cytokeratin 8/18, albeit at lower levels than luminal carcinomas, as well as KIT, which is expressed by luminal ER-negative epithelia [45].…”
Section: Class Discovery Studies: Moving Away From Histopathology?mentioning
confidence: 99%
“…NET TMA sections (5 m) were analyzed by FISH for EGFR and HER-2/neu copy number by the Cytogenetics Shared Resource Laboratory, Mayo Clinic Rochester, as reported (Gilbert et al 2008). Thirty nuclei were scored per sample with quantitation of red signals (HER-2/neu or EGFR) and green signals (chromosome 17 centromere (CEP17) or chromosome 7 centromere (CEP7) respectively).…”
Section: Fish Analysis Of Gene Copy Numbermentioning
confidence: 99%
“…All neuroendocrine tumor tissues assessed for EGFR, KIT, PDGFRA, and KRAS mutations are listed, by case, in Supplementary Table S1. Mutational analyses of EGFR (exons 18, 19, and 21) were performed as previously described (Gilbert et al 2005); KIT mutational analyses (exons 9, 11, 13, and 17) were conducted as reported (Gilbert et al 2008).…”
Section: Fish Analysis Of Gene Copy Numbermentioning
confidence: 99%